Gambaran strategi koping orang tua dengan anak retardasi mental - Fatimah Nuralami; Iceu Amira Dira Atmadja; Gusgus Ghraha Ramdhanie (Holistik Jurnal Kesehatan, 2022)
Background: Poor parents' coping strategy can causes behavioral disorders that occur in parents and will also have an impact on child care such as neglecting, depression in parents and social isolation in the children.Purpose: To find out how the description of coping strategy of parents with mental retardation children.Method:This study was conducted descriptive quantitative, describing coping strategies of parents with mentally retarded children in the State SDLB 2 Garut City. Its population is the elderly mentally retarded child who totaled 89 people. The number is a combination of 46 parents consisting of 43 pairs of father and mother and also 3 single parents. Sampling with total population technique. The instrument used in this study is Coping Health Inventory for Parent.Results: Shows that most of the coping strategy of parents were in the maladaptive category as many as 51.7%. Whereas in the dimensions of coping strategy, most of them showed maladaptive. As many as 55.1% in the family integrity dimension, 52.8% in the psychological stability dimension and 50.6% in the communication dimension.Conclusion: It is recommended that parents improve the coping strategy to collaborate between partners or families, maintain psychological stability and communicate with people who have the same problem or are in the middle of health. It is hoped that nurses can provide counseling to parents to help improve coping strategies.Keywords: Parents; Coping Strategy; Child; Mental RetardationPendahuluan :  Strategi coping orang tua yang buruk dapat menyebabkan gangguan perilaku yang terjadi pada orang tua dan juga akan berdampak pada pengasuhan anak seperti penelantaran, depresi pada orang tua dan isolasi sosial pada anak.Tujuan: Untuk mengetahui bagaimana gambaran strategi koping orang tua dengan anak tunagrahita.Metode: Penelitian ini dilakukan secara deskriptif kuantitatif, mendeskripsikan strategi koping orang tua dengan anak tunagrahita di SDLB Negeri 2 Kota Garut. Populasinya adalah lansia anak tunagrahita yang berjumlah 89 orang. Jumlah tersebut merupakan gabungan dari 46 orang tua yang terdiri dari 43 pasang ayah dan ibu serta 3 orang tua tunggal. Pengambilan sampel dengan teknik populasi total. Instrumen yang digunakan dalam penelitian ini adalah Inventarisasi Coping Kesehatan Orang Tua.Hasil: Menunjukkan bahwa sebagian besar strategi koping orang tua berada pada kategori maladaptif yaitu sebanyak 51,7%. Sedangkan pada dimensi strategi koping sebagian besar menunjukkan maladaptif. Sebanyak 55,1% pada dimensi integritas keluarga, 52,8% pada dimensi stabilitas psikologis dan 50,6% pada dimensi komunikasi.Simpulan: Disarankan kepada orang tua meningkatkan strategi koping untuk berkolaborasi antara pasangan atau keluarga, menjaga stabilitas psikologis dan berkomunikasi dengan orang yang memiliki masalah yang sama atau berada di tengah kesehatan. Diharapkan perawat dapat memberikan konseling kepada orang tua untuk membantu meningkatkan strategi koping.